A general strategy to construct yolk-shelled metal oxides inside carbon nanocages for high-stable lithium-ion battery anodes. (February 2020) - Liu, Meng; Fan, Hao; Zhuo, Ou; Chen, Junchao; Wu, Qiang; Yang, Lijun; Peng, Luming; Wang, Xizhang; Che, Renchao; Hu, Zheng
Abstract: Metal oxides (MOs) are attractive anode materials of Li-ion batteries for the large theoretical capacity, low cost and high density, but suffer from the poor cycling stability owing to the low conductivity, large volume variation, active component loss and instable solid electrolyte interface (SEI) during cycling. Herein, we develop a simple and general strategy to construct the yolk-shelled metal oxides inside 3D hierarchical carbon nanocages (hCNC). The obtained yolk-shelled MO@hCNC provides sufficient interior void to buffers the large volume variation, forms the stable SEI film, and greatly reduces the loss of active components during lithiation/delithiation, meanwhile ensures the fast electron transfer and ions/electrolyte transportation. Both SnO2 @hCNC and Fe3 O4 @hCNC exhibit superior cycling stability and reversible capacity to the most corresponding SnO2 - and Fe3 O4 -based anode materials reported to date. The simple and general approach to the yolk-shelled MO@hCNC is significant for exploring the high-performance energy-storage materials for Li-ion batteries or even beyond. Graphical abstract: We report a simple and general strategy to construct the yolk-shelled metal oxides (MOs) inside 3D hierarchical carbon nanocages (hCNC). The so-obtained yolk-shelled MO@hCNC provides sufficient interior void to buffer the large volume variation, forms the stable SEI film, and greatly reduces the loss of active components during cycling. All these features lead to the long-term cycling stability, high specific capacity and high-rate performance, far superior to the corresponding counterparts of MO nanoparticles supported outside hCNC (MO/hCNC). Image 1 Highlights: A simple and general strategy to construct yolk-shelled MO@hCNC (MO = SnO2, Fe3 O4 ). The yolk-shelled MO@hCNC samples are excellent anode materials for LIBs. The performance structure correlation is well demonstrated.